Matching e determinaç\~ao de contratos nas micro empresas no Brasil - Joana C. M. Monteiro; Juliano J. Assunç\~ao (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2005)
– This paper explores the ECINF database, a survey conducted by the Brazilian Census Bureau that investigates micro-enterprises in Brazil. The linked employeremployee nature of the data was used to study the issue of matching between employers and employees. The results indicate the presence of matching in the labor contracts. There is evidence that employers tend to contract workers with the same gender, age and educational level. Moreover, it is shown that this matching affects the contract form. People with the similar characteristics prefer share contracts.
Keywords: 330; assortative matching; contracts; micro enterprise